2017
DOI: 10.1186/s12904-017-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led navigation to provide early palliative care in rural areas: a pilot study

Abstract: BackgroundFew services are available to support rural older adults living at home with advancing chronic illness. The objective of this project was to pilot a nurse-led navigation service to provide early palliative support for rural older adults and their families living at home with advancing chronic illness.MethodsTwenty-five older adults and 11 family members living with advancing chronic illness received bi-weekly home visits by a nurse navigator over a 2-year period. Navigation services included symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 39 publications
2
54
0
10
Order By: Relevance
“…(31)(32)(33) Another strategy to contain costs and facilitate patient referral and follow-up would be the employment of patient navigators, who have been proven to reduce unnecessary emergency department visits and readmissions in other settings. (34,35) Our findings support those of previous studies that demonstrated the importance of hospital-level characteristics to outcomes among patients with cirrhosis. (7,8) Mellinger et al found that patients admitted to rural hospitals had a 27% higher odds of in-hospital mortality than patients admitted to urban hospitals after accounting for patient-level factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(31)(32)(33) Another strategy to contain costs and facilitate patient referral and follow-up would be the employment of patient navigators, who have been proven to reduce unnecessary emergency department visits and readmissions in other settings. (34,35) Our findings support those of previous studies that demonstrated the importance of hospital-level characteristics to outcomes among patients with cirrhosis. (7,8) Mellinger et al found that patients admitted to rural hospitals had a 27% higher odds of in-hospital mortality than patients admitted to urban hospitals after accounting for patient-level factors.…”
Section: Discussionsupporting
confidence: 89%
“…Subspecialty care through dispersed networks have shown telemedicine and spoke‐and‐hub referral systems to be highly cost‐effective in other disease settings . Another strategy to contain costs and facilitate patient referral and follow‐up would be the employment of patient navigators, who have been proven to reduce unnecessary emergency department visits and readmissions in other settings …”
Section: Discussionmentioning
confidence: 99%
“…For people having one of the cancers associated with the longest survival times who die of non-cancer causes, the median interval from last navigation visit to death is about 4 years (breast cancer, 223 weeks; colorectal cancer, 203 weeks; prostate cancer, 195 weeks); for people having one of the cancers associated with the shorter survival times, the interval is less than 1 year (esophageal cancer, 41 weeks; pancreatic cancer, 29 weeks). Navigation by nurses 40 or volunteers 41,42 might provide an ideal means to increase advance care planning for people dying of non-cancer conditions, especially those with advancing non-cancer diseases whose navigation rates are less than 20% (Table ii).…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that in remote areas, nurses are usually limited in resources and support, ICTs represent a viable channel to increase access and equity to health care information and services [28]. For instance, a pilot study found that the quality of life for older, rural adults and family members living at homes with advancing chronic illness, improved with early palliative support of a nurse navigator, not only through visits but also through cellphone consultations [29]. Telehealth technologies then, through the use of a wide array of ICTs, can provide a platform for remote patient monitoring, videoconferencing, and computer-mediated communications [30].…”
Section: Discussionmentioning
confidence: 99%